PENGARUH TATA KELOLA PERUSAHAAN DAN KINERJA LINGKUNGAN TERHADAP NILAI PERUSAHAAN PADA INDUSTRI DASAR DAN KIMIA YANG TERDAFTAR DI BEI TAHUN 2014 – 2016 - Mufidah Mufidah (Universitas Batanghari Jambi, 2018)
This research aimed to examine the influence of corporate governance and environmental performance to firm value in basic and chemical industry . Corporate governance was identified by the proportion of independent commissioner board, and number of audit committee. Firm value was proxied by Tobin’s Q (market-based financial performance), while environmental performance was measured by PROPER issued by the Indonesian State Ministry of Environmental. The study used 26 companies as a sample from a population of 64 companies in basic and chemical industry listed on Indonesian Stock Exchange in the period of 2014-2016. The sample was determined by using purposive sampling. The results showed that corporate governance mechanisms proxied by the proportion of independent commissioner board, and number of audit committee had positive effect on firm value. Beside that, these results proved that there was positive effect of environmental performance on firm valueKeywords: corporate governance, environmental performance, firm value